The Importance of Spin State in Chiral Supramolecular Electronics - Garcia, Ana M.; Martínez, Gabriel; Ruiz-Carretero, Amparo (Frontiers in Chemistry, 2021)
The field of spintronics explores how magnetic fields can influence the properties of organic and inorganic materials by controlling their electron’s spins. In this sense, organic materials are very attractive since they have small spin-orbit coupling, allowing long-range spin-coherence over times and distances longer than in conventional metals or semiconductors. Usually, the small spin-orbit coupling means that organic materials cannot be used for spin injection, requiring ferromagnetic electrodes. However, chiral molecules have been demonstrated to behave as spin filters upon light illumination in the phenomenon described as chirality-induced spin selectivity (CISS) effect. This means that electrons of certain spin can go through chiral assemblies of molecules preferentially in one direction depending on their handedness. This is possible because the lack of inversion symmetry in chiral molecules couples with the electron’s spin and its linear momentum so the molecules transmit the one preferred spin. In this respect, chiral semiconductors have great potential in the field of organic electronics since when charge carriers are created, a preferred spin could be transmitted through a determined handedness structure. The exploration of the CISS effect in chiral supramolecular semiconductors could add greatly to the efforts made by the organic electronics community since charge recombination could be diminished and charge transport improved when the spins are preferentially guided in one specific direction. This review outlines the advances in supramolecular chiral semiconductors regarding their spin state and its influence on the final electronic properties.